2006
DOI: 10.1128/jvi.80.1.526-536.2006
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus Vpx Is Imported into the Nucleus via Importin Alpha-Dependent and -Independent Pathways

Abstract: Vpx protein of human immunodeficiency virus type 2/simian immunodeficiency virus (SIV) has been implicated in the transport of the viral genome into the nuclei of nondividing cells. The mechanism by which Vpx enters the nucleus remains unknown. Here we have identified two distinct noncanonical nuclear localization signals (NLSs) in Vpx of SIV smPbj1.9 and defined the pathways for its nuclear import. Although nuclear targeting signals identified here are distinct from known nuclear import signals, translocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…GFP fusions containing different Vpx deletion fragments expressed in either HeLa or Cos-7 cells were found to localize differentially (GFPVpx1-63 in the cytoplasm and GFP-Vpx20-40 in the nucleus) (48). This indicated the presence of NES in SIVsm Vpx.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…GFP fusions containing different Vpx deletion fragments expressed in either HeLa or Cos-7 cells were found to localize differentially (GFPVpx1-63 in the cytoplasm and GFP-Vpx20-40 in the nucleus) (48). This indicated the presence of NES in SIVsm Vpx.…”
Section: Resultsmentioning
confidence: 94%
“…SH3 domains of Fyn, Src, Hck, full-length Crk, and importin-␤ as glutathione transferase (GST) fusion proteins were expressed in E. coli BL21(DE3) or M15-prap4 cells and purified as described previously (48). GFP and GFP-Vpx (full length) were synthesized using […”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we performed in vitro GST pull-down competition assays (data not shown). In these studies, GST-Gag was used to bind 35 Slabeled Vpx in the presence of increasing amounts of Histagged Hsp40/DnaJB6. The result demonstrated that a reduced amount of Vpx was captured by GST-Gag when Histagged Hsp40/DnaJB6 was preincubated with Vpx, suggesting that Hsp40/DnaJB6 competes with Gag for binding to Vpx.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, N-terminal (residues 20 to 40) and C-terminal residues (101 to 112) may also affect the nuclear import of Vpx (20,26,35). It has been suggested that importins ␣ and ␤ contribute to this activity (35). Although expression of Vpx, in the absence of other viral proteins, results in a predominant nuclear localization, coexpression of the Pr55 Gag precursor protein shifts Vpx to the plasma membrane and virus particles (26,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation